Evaluasi Sistem Manajemen Kinerja Pengendalian Dan Operasi Dinas Pemadam Kebakaran Dan Penyelamatan Dalam Penanggulangan Bencana Kebakaran Di Kota Pekanbaru - Nursani Aprilya; Hafzana Bedasari (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The rapid urbanization in Pekanbaru City demands fast, effective, and responsive fire management services. This study aims to evaluate the performance management system of the Control and Operations Division of the Pekanbaru Fire and Rescue Department during the 2022–2024 period and to identify obstacles in its implementation. This study employed a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, and then analyzed using Stufflebeam's CIPP Evaluation Model (Winaryati et al., 2021 )which includes the aspects of context, input, process, and product. The findings indicate that, in the context aspect, the performance management system has supported the organization’s vision and mission, although its implementation still faces several challenges. In the input aspect, limitations in facilities and infrastructure, uneven personnel competencies, and insufficient operational budgets were identified. In the process aspect, operational activities have been carried out, but inter-agency coordination has not yet been optimally integrated. In the product aspect, the response time achievement of 82–91% and a Community Satisfaction Survey score of 95.09 indicate positive outcomes, although service distribution has not been fully optimized across all areas of the city. This study recommends improving operational facilities, strengthening personnel competencies, expanding the distribution of fire stations, and developing an integrated emergency coordination system to enhance the effectiveness of fire management services.